Communicating efficacy information based on composite scores in direct-to-consumer prescription drug advertising. Issue 4 (April 2016) - Williams, Pamela A.; O'Donoghue, Amie C.; Sullivan, Helen W.; Willoughby, Jessica Fitts; Squire, Claudia; Parvanta, Sarah; Betts, Kevin R.
Highlights: A composite score is a combination of multiple components of drug efficacy measurement. This is the first study to examine DTC ad composite score comprehension. Ads with a composite score definition alone improved composite score comprehension. Ads with an educational intervention improved comprehension. Abstract: Objective: Drug efficacy can be measured by composite scores, which consist of two or more symptoms or other clinical components of a disease. We evaluated how individuals interpret composite scores in direct-to-consumer (DTC) prescription drug advertising. Methods: We conducted an experimental study of seasonal allergy sufferers ( n = 1967) who viewed a fictitious print DTC ad that varied by the type of information featured (general indication, list of symptoms, or definition of composite scores) and the presence or absence of an educational intervention about composite scores. We measured composite score recognition and comprehension, and perceived drug efficacy and risk. Results: Ads that featured either (1) the composite score definition alone or (2) the list of symptoms or general indication information along with the educational intervention improved composite score comprehension. Ads that included the composite score definition or the educational intervention led to lower confidence in the drug's benefits. The composite score definition improved composite score recognition and lowered drug risk perceptions. Conclusion: Adding composite score information to DTC print ads may improve individuals' comprehension of composite scores and affect their perceptions of the drug. Practice implications: Providing composite score information may lead to more informed patient-provider prescription drug decisions.